The Influence of Promotion, Word of Mouth, and Brand Image on The Purchase Decision of Local Sangihe Product Kofo - Lolaroh, Stefanie M. E.; Nelwan, Olivia S.; Tumbuan, Willem J.F. Alfa (Abdurrauf Science and Society, 2025)
The fashion industry significantly contributes to national economic development, particularly through micro, small, and medium enterprises (MSMEs). According to data from CNBC Indonesia cited by Bina Nusantara University (2019), the sector accounted for 3.76% of Indonesia’s GDP in 2017, with export earnings reaching USD 13.29 billion. In 2016, the fashion subsector was the largest contributor to the creative economy at 54.54%. North Sulawesi, rich in cultural heritage, offers traditional textiles such as Kofo Sangihe, which reflect local identity and creative potential. This study aims to examine the effects of promotion, word of mouth (WOM), and brand image on consumer purchase decisions of Kofo Sangihe products. A quantitative associative approach was used, involving 73 respondents who had purchased the product. Regression analysis indicates that all three variables simultaneously have a significant positive effect on purchase decisions (R² = 64.2%). Partially, WOM and brand image show significant influence, while promotion has a positive but lesser impact. The findings highlight the importance of interpersonal communication and culturally rooted brand identity in consumer behavior. Kofo Sangihe thus demonstrates strong potential to grow as a competitive local fashion brand within Indonesia’s creative economy.